OSCE revision for the final FRCEM - Goss, Rachel; McMaster, Emma; Rennie, Stephanie (Oxford : Oxford University Press, 2021)
A comprehensive guide to the Final FRCEM examination,'OSCE Revision for the Final FRCEM' covers over 100 topics in emergency medicine. It is mapped to the curriculum for the Royal College of Emergency Medicine, and is structured by the domains in the syllabus.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 24, 2021).
Keywords: Royal College of Emergency Medicine (Great Britain) -- Examinations -- Study guides; Emergency medicine -- Examinations -- Study guides; Emergency medicine -- Examinations, questions, etc